Invariant tori of differential equations in a Banach space - Ilolov, M.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish conditions for the existence, uniqueness, and smoothness of the toroidal manifolds of differential equations with unbounded operator coefficients.